White Spot on the Back. Issue 5 (September 2015) - Sandhu, Amandeep S.; Jacob, Sharon E.
<x xml:space="preserve">Abstract</x> ABSTRACT Teledermatology is a term to describe the provision of dermatologic medical services through telecommunication technology. In this modality, there is transfer of medical information electronically (including history and visual data) on a patient in one location to a provider who is in another location. The construct of this column is such that cases are presented in a standardized teledermatology reader format. This is a case of a white spot on the back.